1999
DOI: 10.1162/108819899569584
|View full text |Cite
|
Sign up to set email alerts
|

The Mixing Triangle: Correlation and Graphical Decision Support for LCA‐based Comparisons

Abstract: Summary Recent developments within life‐cycle impact assessment (LCIA) allow direct modeling of changes to predefined safeguard subjects that represent the environment to be protected. These changes are often expressed in a few damage indicators and calculated for each product alternative to be compared. This article analyzes the correlation among damage indicators within one specific LCIA methodology, assesses the implications of such correlation for the use of weighting methods, and proposes a method for gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 9 publications
(5 reference statements)
0
55
0
4
Order By: Relevance
“…Another possible solution is aggregating the impact categories into a new indicator by scoring and weighting beforehand. Hofstetter et al [30] show the aggregation of different environmental impacts, i.e., pesticides, greenhouse effects, acidification, and eutrophication, based on a universal scoring method in the Eco-indicator 95 in a study of mixing triangles application. This aggregated indicator can be easily adapted to our decision support framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible solution is aggregating the impact categories into a new indicator by scoring and weighting beforehand. Hofstetter et al [30] show the aggregation of different environmental impacts, i.e., pesticides, greenhouse effects, acidification, and eutrophication, based on a universal scoring method in the Eco-indicator 95 in a study of mixing triangles application. This aggregated indicator can be easily adapted to our decision support framework.…”
Section: Discussionmentioning
confidence: 99%
“…The mixing triangle method is developed based on the methodologies of Bayesian decision analysis [28,29] and the mixing triangle graphical representation [30,31]. Here, the mixing triangle is aimed at supporting the decision of feed input revision.…”
Section: Mixing Triangle For Supporting Feed Input Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…A model is suggested by the Research Group of The University of Stuttgart which adds to the variables of life cycle engineering (environmental, economic and technological) the variable "capital" or adding it as a fourth variable. Another understandable communication tool, even for nonexperts, is represented by the revision of "The Mixing Triangle" proposed by Hofstetter [33], through the Life Cycle Sustainability Triangle or model of communication of the results proposed by Finkbeiner et al [6], and finally the model suggested by Calcas international project, coordinated by ENEA with the aim of connecting the instruments of Life Cycle Thinking and make them more consistent with the wider concept of sustainable development to define a "new LCA" that included all variables [34].…”
Section: Lcsa = E-lca + Lcc + S-lcamentioning
confidence: 99%
“…Ambas herramientas proporcionan una forma transparente de ponderar los resultados de forma cuantitativa. La primera se propone para facilitar la ponderación de resultados cuando hay tres dimensiones (como en la sostenibilidad) y fue desarrollada inicialmente por Hofstetter et al (1999) su capacidad de presentar resultados por cada indicador o agregados mediante un índice, y la visualización gráfica de dichos resultados (mediante un cartograma). Halog y Manik (2011) proponen una metodología que combina distintos métodos usados por los ecologistas industriales y los economistas biofísicos.…”
Section: Agregación Ponderación E Interpretación De Resultadosunclassified